The relative risk of aortic aneurysm in patients with giant cell arteritis compared with the general population of the UK. Issue 1 (4th October 2013) - Robson, Joanna C; Kiran, Amit; Maskell, Joe; Hutchings, Andrew; Arden, Nigel; Dasgupta, Bhaskar; Hamilton, William; Emin, Akan; Culliford, David; Luqmani, Raashid A
Abstract : Objectives: To evaluate the risk of aortic aneurysm in patients with giant cell arteritis (GCA) compared with age-, gender- and location-matched controls. Methods: A UK General Practice Research Database (GPRD) parallel cohort study of 6999 patients with GCA and 41 994 controls, matched on location, age and gender, was carried out. A competing risk model using aortic aneurysm as the primary outcome and non-aortic-aneurysm-related death as the competing risk was used to determine the relative risk (subhazard ratio) between non-GCA and GCA subjects, after adjustment for cardiovascular risk factors. Results: Comparing the GCA cohort with the non-GCA cohort, the adjusted subhazard ratio (95% CI) for aortic aneurysm was 1.92 (1.52 to 2.41). Significant predictors of aortic aneurysm were being an ex-smoker (2.64 (2.03 to 3.43)) or a current smoker (3.37 (2.61 to 4.37)), previously taking antihypertensive drugs (1.57 (1.23 to 2.01)) and a history of diabetes (0.32 (0.19 to 0.56)) or cardiovascular disease (1.98 (1.50 to 2.63)). In a multivariate model of the GCA cohort, male gender (2.10 (1.38 to 3.19)), ex-smoker (2.20 (1.22 to 3.98)), current smoker (3.79 (2.20 to 6.53)), previous antihypertensive drugs (1.62 (1.00 to 2.61)) and diabetes (0.19 (0.05 to 0.77)) were significant predictors of aortic aneurysm. Conclusions: Patients with GCA have a twofold increased risk of aortic aneurysm, and this should be considered within the range of other risk factors including male gender, age and smoking. A separate screening programme is not indicated. The protective effect of diabetes in the development of aortic aneurysms in patients with GCA is also demonstrated.